Program Pendampingan Keluarga Anak Baduta stunting: Implementasi Interprofesional Collaboration (IPC) di Desa Beka, Marawola, Kabupaten Sigi: Family Assistance Program for Stunted Children: Implementation of Interprofessional Collaboration (IPC) in Beka Village, Marawola, Sigi District - Hafid, Fahmi; Adhyanti, Adhyanti; Eka Cahyani, Yayuk; Faisal, Iskandar; Nasrul, Nasrul; Ramadhan, Kadar; Taqwin, Taqwin; Taufiqurrahman, Taufiqurrahman (Jurnal Pengabdian Masyarakat: Svasta Harena, 2024)
Stunting remains a serious public health issue in Indonesia. The Family Assistance Program for Stunted Children under two years old with the Implementation of Interprofessional Collaboration in Beka Village, Marawola, Sigi District aims to implement Family Assistance for Stunted Children within the context of Interprofessional Collaboration to reduce stunting prevalence in Beka Village, Sigi District. Partners in this community service initiative include the Beka Village Head, Posyandu Cadres, Midwives, Nutritionists, and Marawola Community Health Center Doctors. Community service methods involve collaboration among various healthcare professions Midwives, Nurses, Sanitarians, Nutritionists, Doctors and community members such as Cadres, PKK Mothers, and Village Officials. Implemented in Beka Village, Marawola District, Sigi District, from January 10-31, 2024. It began with a Focus Group Discussion between the Service Providers from the Health Polytechnic of the Ministry of Health in Palu and the Beka Village Head, followed by education for 20 mothers of stunted children and 10 Posyandu cadres, and a 15-day Family Assistance for Stunted Children. The Service Providers handed over 2 anthropometric measuring tools and healthy snack bars to the Beka Village Government. Results of community service showed increased knowledge and healthy behaviors among toddler families and a decrease in stunting rates in Sigi District. The conclusion of this program is that Interprofessional Collaboration can be an effective model in addressing stunting at the community level.